Cutter Load Distribution Analysis and Crown Shape Optimal Design of Complex Curved PDC Bit - Ju Pei (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
When drilling in hard rock formations, the wear of the complex curved PDC bit is extremely uneven. To solve this problem, a numerical simulation method was used to analyze the load distribution law of the cutters and the crown shape of the complex curved PDC bit was optimized. The simulation results showed that: 1) along the radial direction of the bit, the axial load on the cutters increased first and then decreased, while the radial load decreased first and then increased; 2) the axial load on the cutters was the largest at the nose and taper area of the bit, while the radial load on the cutters was the largest at the center and shoulder area of the bit; 3) the influence of the inner cone angle on the cutting load was mainly concentrated in the bit crown's inner cone area, while the influence of the outer arc radius on the cutting load was mainly concentrated in the bit crown nose and taper areas. Based on these conclusions, the crown shape of the complex curved PDC bit was optimized and a field test was carried out. The test results showed that, compared with the original complex curved PDC bit, the average bit life and drilling efficiency of the new designed bit was increased by 20% and 18%, respectively, especially in hard rock drilling. The average drilling efficiency of the new designed bit was increased by 50%.